2018
DOI: 10.1371/journal.pone.0209778
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of near point of care Cepheid GeneXpert HIV-1 Qual for early infant diagnosis

Abstract: BackgroundAccess to point-of-care HIV testing shortens turn-around times, time to diagnosis and reduces loss to follow-up hence minimizing barriers to early linkage to care and treatment among HIV infected infants. Currently samples for early infant HIV diagnosis are sent to centralized testing facilities which are few and located only at specific regions in Kenya. However, there are Point of Care (POC) early infant diagnosis [EID] technologies elsewhere such as SAMBA and ALERE-Q that are yet to be evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 26 publications
1
19
1
Order By: Relevance
“…The proportions with POC EID error/invalid results in our study were higher than proportions of up to 9.3% reported in other studies [9,12,20‐21,24]. Among the EID error/invalid results, 50.2% were associated with cartridges belonging to three specific lots which may suggest faulty cartridges.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…The proportions with POC EID error/invalid results in our study were higher than proportions of up to 9.3% reported in other studies [9,12,20‐21,24]. Among the EID error/invalid results, 50.2% were associated with cartridges belonging to three specific lots which may suggest faulty cartridges.…”
Section: Discussioncontrasting
confidence: 76%
“…POC VL testing improves turn‐around time (TATs) and retention in care among adults on ART [8], while POC EID testing reduces TATs and time to ART initiation in infants [9‐14]. Both have potential to reduce morbidity and mortality among pregnant WLHIV and their infants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…POC diagnostic technologies such as GeneXpert HIV-1 Qual [ 15 ] and Alere m-PIMA [ 16 ] are cartridge-based tests that can be processed at the hospital by trained clinical or laboratory staff and can result in more rapid turnaround times of results, more infants being identified as HIV-positive and more infants initiated on ART at younger ages than traditional testing strategies [ 17 22 ]. Studies have shown high sensitivity and specificity of POC testing and found that POC implementation is feasible in hospital-based settings in Kenya [ 23 , 24 ], South Africa [ 18 , 25 27 ], Mozambique [ 28 ], and Tanzania [ 29 ]; is acceptable to providers [ 26 ] and patients [ 30 ]; and may be a cost-effective option for EID [ 31 , 32 ]. Based on the promising evidence supporting POC, the World Health Organization (WHO) conditionally recommended the introduction of POC for EID in 2016 [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…GeneXpert systems by Cepheid is a near POCT NAAT that relies on hemi-nested qualitative PCR. GeneXpert HIV-1 Qual and GeneXpert MTB/RIF panels are currently being used for early infant HIV diagnosis and MTB/Rifampicin detection (Saeed et al, 2017 ; Opollo et al, 2018 ). With the ongoing COVID-19 pandemic, Xpert Xpress SARS-Cov2 test by Cepheid was the first to be approved by FDA for coronavirus testing and can produce results in about 45 min (Opollo et al, 2018 ).…”
Section: Commonly Employed Poct Technologiesmentioning
confidence: 99%